REFLECTION OF SAJ’I MUTARRAF USED IN THE TEXT "BOBURNOMA" IN ENGLISH TRANSLATION (Scientific journal of the Fergana State University, 2023)
This article discusses about the translation of the rhyming saj’s in the "Boburnoma" that were originally used in the translations made by English and American translators (Leyden-Erskine, A.S. Beveridge and W. Thackston). The skill of the translator, the scholar of oriental literature, the style of the original author, the reflection of the national identity and the spirit of the time in the translation are expressed. It is also explained about the translator's skill of choosing words, the important aspects of preserving the spirit of the original in the translation and reflecting it in the translation.